Achalasia of the cardia in elderly patients. Issue 634 (August 1978) - Lock, M. R.; Ellis, H.
Abstract : Achalasia of the cardia frequently presents as dysphagia in middle age. In the elderly, dysphagia is usually due to a neoplasm of the oesophagus or cardia. The authors have been interested to see five patients over the age of 70 presenting with oesophageal symptoms due to achalasia which is uncommon in this age group and may be mistaken for neoplastic disease.